Pre-Reading strategies on Reading comprehension of EFL Students - Malikhatul Lailiyah; Prilla Lukis Wediyantoro; Karlina Karadila Yustisia (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2019)
This study investigated the role of background knowledge or schema in reading comprehension of the EFL students. Based on schema theory, comprehending a text is an interactive process between the reader’s background knowledge and the text. Therefore, to understand the text better, the reader should has enough background knowledge. This study focuses on three pre-reading strategies: pre-teaching new vocabularies, pictorial context, and pre-reading questioning. Participants were 46 students in two groups: experimental and control class. Before the treatment, in order to assess their knowledge of reading comprehension, a pre-test was given in both groups. During the treatment, experimental group received pre-reading strategies before reading the text, but control group did not. In analysing the data, independent t-test was used. The result indicated that there is significant difference between students who are exposed to pre-reading strategies and those who did not. DOI: 10.26905/enjourme.v4i2.3954